Applying Design Thinking to Develop Motion Graphics for Enhancing Digital Literacy Education Among the Elderly - Nguenruangrot, Phitchapon; Yamcharoen, Nattapong (Siam Communication Review, 2025)
The purpose of this research is to study design thinking for creating motion graphics in digital learning and teaching for older adults. The design thinking approach was applied following five stages: 1) Empathize, 2) Define, 3) Ideate, 4) Prototype, and 5) Test. Data was collected from a target group of 20 participants, consisting of 10 older adults, 5 professionals, and 5 academics, in order to produce motion graphic media for teaching and learning for older adults. The data was analyzed based on the research objectives. The research findings indicate that design thinking can aid in creating media that addresses the real problems and needs of older adults, thus enhancing the effectiveness of teaching materials in promoting learning. The design thinking process was applied, starting with empathizing to understand the physical challenges of older adults, followed by clearly defining the problem based on this understanding. The creation of motion graphic media focused on five key elements: imagery, sound, scenes, and typography, leading to the production of video content and the identification of suitable solutions. The prototype was tested on YouTube, and the feedback from the three target groups was analyzed. The analysis focused on two aspects: 1) the motion graphics in digital learning for older adults, which received positive evaluations; and 2) the quality of the motion graphics in digital learning, where the three target groups showed differing opinions. The highest rating was for the clarity of voice-over and the accuracy of the text, while the lowest rating was related to the use of color.